Comparison of wound closure techniques in median sternotomy scars in children: subcuticular suture versus Steri-Strip™ S. Issue 3 (4th May 2019) - van de Kar, Annekatrien L.; Koolbergen, David R.; van Avendonk, Janne P. H.; van der Horst, Chantal M. A. M.
Abstract: Objectives: The aim of this retrospective study was to compare subcuticular sutures and Steri-Strip™ S in closing median sternotomy incisions in children with regard to wound healing and scar formation. Methods: Fifty-three children and adolescents were enrolled in this study who all underwent a median sternotomy at age 0–18 years and had their presternal cutaneous wounds closed with either a running subcuticular suture (Group 1) or Steri-Strip™ S (Group 2). Their scars were assessed using the Patient and Observer Scar Assessment Scale (POSAS). Secondary outcome measures were the scar measurements and the incidence of wound problems post-surgery. Results: A significant difference was found between both groups in median POSAS observer scale scores for the items thickness ( p  = .027), pliability ( p  = .045), surface area ( p  = .045) and the total score ( p  = .048). All in favor of the subcuticular suture group. There were no significant differences concerning the POSAS patient scale scores. Middle parts of scars of patients in Group 2 were significantly broader ( p  = .001) than scars of patients in Group 1. No significant differences concerning wound problems were found. Conclusions: There are, according to our results, no significant differences in wound healing of median sternotomy incisions in children closed with either a subcuticular suture or Steri-Strip™ S. Significant differences do exist regarding scar formation and final cosmetic results of the scars, in favor of subcuticular closure.